Ang lihim ni Antonio Antonio's secret - Bonife, Lex; Altarejos, Joselito; Del Rosario, Vicente; Del Rosario, Vic Jr (Viva platinum, 2008)
"Antonio is a 15-year old boy who begins to ponder on the purpose of his life and his identity. For a smart teenager at this stage, he has begun to confront the issues of his personality, the struggle of acceptance from his peers, his family on the verge of breaking up and the sudden flare of his homosexual urges. Antonio's mother, Tere, a community midwife, is in continuous denial that her husband has left them for another family. Antonio's life begins to take a dangerous turn as his uncle Jonbert, a hedonistic and carefree young man, begins to live with them and makes the young boy his sexual plaything. But Antonio is caught unprepared for things that would be, and in a sudden fit of rage, Tere does the unthinkable."--Container.